FAKTOR-FAKTOR PEMERIKSAAN DAN LAINNYA YANG MEMENGARUHI AUDIT REPORT LAG - MERRY YOHANES; RUDI SETIADI TJAHJONO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
The objective of this research is to provide empirical evidence regarding the factors that influence audit report lag. These factors include company size, audit firm status, board size, audit committee, ownership dispersion, ownership concentration, audit tenure, audit committee expertise, and audit committee meetings. The population of this study is manufacturing companies listed in Indonesia Stock Exchange during the period of 2018 to 2020. The sample in this study is selected based on the purposive sampling method. The number of sample in this study that meets the sampling criteria is 339 data. This research is using multiple regression analysis. The results of this research indicate that board size and audit committee expertise have a negative effect on audit report lag, while ownership dispersion, ownership concentration, and audit tenure have a positive effect on audit report lag. However, the variables of firm size, audit firm status, audit complexity, audit committee, and audit committee meetings have no effect on audit report lag.